Tatwiiri Wasaait Lu’bah Tsu’bani Wa Salam Litarqiyati Rugbati Ta’allumil Lughati al-Arabiyati Fii al-Madrasati al-Diniyati at-Ta’liimiyati Zainul Hasan Genggong - Zainullah, Ahmad; Kamelia, Faridatul; Farid, Edi Kurniawan (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This development research aims to determine the validity and effectiveness of the Arabic Snakes and Ladders game media to increase interest in learning Arabic. The research method used is research and development with the (4-D) model. The research sample consisted of 29 even semester female students of the Zainul Hasan Genggong Islamic Boarding School. The data collection technique for this research was obtained from the analysis of validation scores, and learning interest questionnaires (pre-test and post-test). The search results for the Arabic Snakes and Ladders game media met the truth criteria by obtaining an overall score reviewed from the language examiner's assessment of 97% and from the media examiner of 98% with a very valid category. Therefore, it is suitable for use based on expert reviews. The Arabic Snakes and Ladders game mode meets the effectiveness criteria, namely by looking at the average score of the results of the learning interest questionnaire analysis of 80% with a very high category. Based on these data, the Arabic Snakes and Ladders game mode can be said to be of high quality because it meets the criteria for validity and effectiveness. Based on the results of the study, the researcher suggests that the Arabic Snakes and Ladders media can be used as an educational method in learning Arabic. Further researchers can continue this research into publications, not only in the form of socialization but also testing it in other schools.